Rapid purification of brain protein complexes containing active and inactive forms of the G protein Gαo - Shubham Yadav; Satya Santoshi Veliventi; Sitaram Meena; Michael R. Koelle; Santosh Kumar (PLoS ONE, 2025)
Gα o is the alpha subunit of the most abundant heterotrimeric G protein of the brain and relays signals from G protein-coupled receptors to inhibit neural function. To date, no direct downstream effectors for Gα o have been well-characterized. Active Gα-GTP proteins should form stable complexes with their effectors, but identifying Gα o effectors by isolating such complexes is a challenge since the vast majority of Gα o in the brain is in its inactive, GDP-bound form. In this study, we developed methods to isolate microgram quantities of native Gα o -GTP protein complexes by immunoprecipitation from brain lysates. We found that native Gα o protein in crude detergent lysates of mouse brain rapidly binds and is activated by the slowly-hydrolyzable GTP analog GTPγS. Using size exclusion chromatography and tracking the Gα o -containing complexes by western blotting, we found that native Gα o in crude brain lysates exists in complexes that change size upon activation by GTPγS. We also identified a monoclonal antibody that can efficiently immunoprecipitate Gα o protein complexes from mouse brain lysates for downstream applications such as mass spectrometry and protein-protein interaction assays. Our results and methods enable further research into the Gα o signaling pathway.